2008
DOI: 10.1007/bf03086173
|View full text |Cite
|
Sign up to set email alerts
|

Conditions mimicking acute ST-segment elevation myocardial infarction in patients referred for primary percutaneous coronary intervention

Abstract: Background/Objectives. A rapid diagnosis of STsegment elevation myocardial infarction (STEMI)is mandatory for optimal treatment. However, a small proportion of patients with suspected STEMI suffer from other conditions. Although case reports have described these conditions, a contemporary systematic analysis is lacking. We report the incidence, clinical characteristics and outcome of patients with suspected STEMI referred for primary percutaneous coronary intervention (PCI) with a final diagnosis other than ST… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
64
3
10

Year Published

2008
2008
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(78 citation statements)
references
References 27 publications
1
64
3
10
Order By: Relevance
“…Earlier reports have elucidated that one-third of cases were initially missed [31] and that AD was clinically suspected only in 15% of patients before death [9] . Although infrequent, AD should enter into the differential diagnosis of patients either presenting with acute chest pain associated with or without arterial hypertension and/or aortic regurgitation or mimicking ST-segment elevation myocardial infarction [21,32] . AD should be differentiated from acute pulmonary embolism and acute coronary syndromes [32] .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Earlier reports have elucidated that one-third of cases were initially missed [31] and that AD was clinically suspected only in 15% of patients before death [9] . Although infrequent, AD should enter into the differential diagnosis of patients either presenting with acute chest pain associated with or without arterial hypertension and/or aortic regurgitation or mimicking ST-segment elevation myocardial infarction [21,32] . AD should be differentiated from acute pulmonary embolism and acute coronary syndromes [32] .…”
Section: Discussionmentioning
confidence: 99%
“…Although infrequent, AD should enter into the differential diagnosis of patients either presenting with acute chest pain associated with or without arterial hypertension and/or aortic regurgitation or mimicking ST-segment elevation myocardial infarction [21,32] . AD should be differentiated from acute pulmonary embolism and acute coronary syndromes [32] . Mehta et al, reported that acute type A-AD as a result of hypertension, atherosclerosis and iatrogenic post cardiac surgery, were commonly found in the elderly (>70 years) [8] .…”
Section: Discussionmentioning
confidence: 99%
“…3 The prevalence of MI associated with normal coronary arteries, which may present diffuse atherosclerotic lesions but a level of stenosis below 30%, is between 1% and 12%. 4 …”
Section: Introductionmentioning
confidence: 99%
“…The paper by Gu et al in this issue of Netherlands Heart Journal emphasises alternative diagnoses encountered in such a liberal admission system of primary PCI. 4 From a group of 820 patients referred for primary PCI they identified 19 alternative diagnoses (2.3%). If we consider only those patients actually treated by primary PCI or emergency coronary bypass surgery as true positive referrals, the number of false positives still amounts to only 5.9%.…”
mentioning
confidence: 99%
“…Obviously adopting a more liberal system will have advantages as well as disadvantages. A benefit may be formed by, but not limited to, early availability of coronary anatomical information and early admission to tertiary centres for complex alternative disorders as shown in the paper by Gu et al 4 A disadvantage will be the infrastructural burden by repeated unjustified activation of the cardiac catheterisation laboratory for more false positives and potentially a longer delay in the diagnostic work-up for non-cardiovascular disorders. It is reassuring in this respect to learn from this paper that the majority of false positives (about two thirds) included cardiovascular diseases that either did not require emergency procedures or were fortunate to be referred to a tertiary centre (e.g.…”
mentioning
confidence: 99%